A comprehensive thermodynamic model for RNA binding by the Saccharomyces cerevisiae Pumilio protein PUF4 - Sadée, Christoph; Hagler, Lauren D.; Becker, Winston R.; Jarmoskaite, Inga; Vaidyanathan, Pavanapuresan P.; Denny, Sarah K.; Greenleaf, William J.; Herschlag, Daniel (Nature communications, 2022)
Genomic methods have been valuable for identifying RNA-binding proteins (RBPs) and the genes, pathways, and processes they regulate. Nevertheless, standard motif descriptions cannot be used to predict all RNA targets or test quantitative models for cellular interactions and regulation. We present a complete thermodynamic model for RNA binding to the S. cerevisiae Pumilio protein PUF4 derived from direct binding data for 6180 RNAs measured using the RNA on a massively parallel array (RNA-MaP) platform. The PUF4 model is highly similar to that of the related RBPs, human PUM2 and PUM1, with one marked exception: a single favorable site of base flipping for PUF4, such that PUF4 preferentially binds to a non-contiguous series of residues. These results are foundational for developing and testing cellular models of RNA-RBP interactions and function, for engineering RBPs, for understanding the biophysical nature of RBP binding and the evolutionary landscape of RNAs and RBPs. Traditional genomic methods identify RNA-binding proteins (RBPs) and the genes they regulate, but do not provide predictive models. The authors used an emerging technology to obtain a complete thermodynamic model for RNA binding to the PUF4 RBP.